Pengaruh Electronic Word Of Mouth, Brand Credibility, Dan Celebrity Endorsement Di Tiktok Terhadap Keputusan Pembelian Produk Glad2glow (Studi Kasus Generasi Z Pada Kecamatan Medan Sunggal) - Ramayana Sinaga; Siti Alhamra Salqaura; Hesti Sabrina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research was conducted with the purpose and objective of determining the influence of electronic word of mouth, brand credibility, and celebrity endorsement on the Purchase Decision of Glad2glow Products (Case Study of Generation Z in Medan Sunggal District). The type of research used in this study is associative research with a quantitative approach. The sampling technique used in this study is non-probability sampling. The sample in this study is Generation Z in Medan Sunggal District. The sample size used is 100 respondents. The data obtained were primary data in the form of questionnaires distributed thru Google Forms and analyzed using the multiple linear regression analysis method with the SPSS 27 program. Based on the hypothesis testing that 1) Electronic word of mouth (X1) has a positive and significant effect with a t-statistic value of 2.570 > t-table 1.984, and a p-value in the sig column of 0.012 < 0.05, which means it has a significant effect. 2) Brand credibility (X2) has a positive and significant effect with a calculated t-value of 2.992 > t-table 1.984, and the p-value in the sig column is 0.004 < 0.05, which means it has a significant effect. 3) Celebrity endorsement (X3) has a positive and significant effect with a t-statistic value of 3.817 > t-table 1.984, and the p-value in the sig column is 0.001 < 0.05, which means it has a significant effect. 4) The purchase decision based on the F-test results shows that the calculated F-value is 56.702 > the F-table value of 3.090 and the significance level is 0.001 < 0.05, which means that electronic word-of-mouth, brand credibility, and celebrity endorsement simultaneously have a positive and significant effect on the purchase decision of Glad2Glow products, a case study of Generation Z in Medan Sunggal District.